Inhibition of Virulence-Related Traits in Pseudomonas syringae pv. actinidiae by Gunpowder Green Tea Extracts - Lovato, Arianna; Pignatti, Annalisa; Vitulo, Nicola; Vandelle, Elodie; Polverari, Annalisa (Frontiers in Microbiology, 2019)
Green tea is a widely-consumed healthy drink produced from the leaves of Camellia sinensis. It is renowned for its antioxidant and anticarcinogenic properties, but also displays significant antimicrobial activity against numerous human pathogens. Here we analyzed the antimicrobial activity of Gunpowder green tea against Pseudomonas syringae pv. actinidiae (Psa), the agent that causes kiwifruit bacterial canker. At the phenotypic level, tea extracts strongly inhibited Psa growth and swimming motility, suggesting it could reduce Psa epiphytic survival during plant colonization. The loss of bacterial virulence-related traits following treatment with tea extracts was also investigated by large-scale transcriptome analysis, which confirmed the in vitro phenotypes and revealed the induction of adaptive responses in the treated bacteria allowing them to cope with iron deficiency and oxidative stress. Such molecular changes may account for the ability of Gunpowder green tea to protect kiwifruit against Psa infection.